Menjelajahi Sifat Antiinflamasi dan Antioksidan Jahe Merah pada Pencegahan Terjadinya Polikistik Ovarium Syndrome (PCOS): Studi In Silico dan In Vivo - Siti Mudrikatin; Herin Herin (The Journal General Health and Pharmaceutical Sciences Research, 2025)
Background of the incident of increasing cases of polycystic ovary syndrome (PCOS) with a prevalence of insulin resistance of 50-75%, insulin resistance will cause oxidative stress due to hyperglycemia which will then increase proinflammatory cytokines in TNF-α and other cytokines, thus triggering an increase in inflammation resulting in an increase in infertility cases of 89.6%. The aim is to investigate the prevention of PCOS through red ginger injected with testosterone propionate in vivo, insilico using open babel software on PyRx V.1.0. The in vivo method is an experimental laboratory study, using two five rats of the rattus norvegicus type divided into five groups using PCOS prevention through red ginger, examinations carried out on blood and ovarian organs, preparations were made which were observed with a binocular microscope on TNF-a examination with immunohistochemistry, ELISA examination on insulin levels, blood examination on blood glucose, data analysis was carried out using one way ANOVA. The study began with the preparation of control activator ligands, 6-Shogaol (Pubchem ID 5281794) and 6-Gingerol (Pubchem ID 442793) and target receptors TNF-α (PDB ID: 2AZ5) and KEAP1-NRF2 (PDB ID: 5CGJ), Insilico results that occur in red ginger are able to interact at a similar position in the interaction of TNF-α with control compared to KEAP1. In vivo research results showed that testosterone propionate 100 mg / kg BW significantly increased the inflammatory cytokine TNF-α, along with polycystic markers in folliculogenesis (p <0.05) compared to negative controls and administration of red ginger at 800 mg / kg significantly decreased TNF-α levels. red ginger also prevents the occurrence of pcos. The conclusion shows that the bioactive 6-shogaol 6-gingerol in red ginger can provide preventive benefits in polycystic ovary syndrome (pcos) by modulating the inflammatory pathway.